Order out of Chaos: The Case for a New Conceptualization of the Cross-Boundary Instruments of American Regionalism. Issue 1 (January 2020) - Miller, David; Nelles, Jen
In the absence of consensus about which organizations matter or are the "right" manifestations of American regional intergovernmentalism scholarship has had to develop an imprecisely defined and tacitly circulated perception of regions and the cross-boundary organizations that embody them. Even where effort has been made to establish a broad and consistent definition for regional cross-boundary organizations these standards have been applied loosely and with notable exceptions. We argue that the lack of conceptual precision and consensus, to date, makes large-scale comparative research difficult and prone to potential blind spots. We offer a framework within which we can unify these different pieces. Rather than focusing on organization type, or geographical scales, we propose a system of identifying and studying regional organizations by five core attributes. We submit these regional intergovernmental organizations (RIGOs) as a conceptual lingua franca that transcends organizational nomenclature and statistical constructs and enables broad, methodologically rigorous, comparative research.